Current therapeutic options in the treatment of rheumatoid arthritis - Köhler, Birgit M.; Günther, Janine; Kaudewitz, Dorothee; Lorenz, Hanns-Martin (Journal of Clinical Medicine, 2019)
Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by chronic inflammation of the joints. Untreated RA leads to a destruction of joints through the erosion of cartilage and bone. The loss of physical function is the consequence. Early treatment is important to control disease activity and to prevent joint destruction. Nowadays, different classes of drugs with different modes of action are available to control the inflammation and to achieve remission. In this review, we want to discuss differences and similarities of these different drugs.